PERAN GURU DALAM MENCEGAH DAN MENANGANI PERILAKU BULLYING PESERTA DIDIK KELAS II DI SD GMIT 25 FANATING - Angely Olivia Atakari; Halena Muna Bekata; Astina Y. Kabbi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to determine the role of teachers in preventing and addressing physical and verbal bullying behavior among second-grade elementary school students. The study was motivated by the continued occurrence of bullying in the school environment, which affects students' comfort, safety, and social-emotional development. The forms of physical bullying identified include pushing, pinching, hitting, and taking classmates' belongings without permission. Meanwhile, verbal bullying includes teasing, giving unpleasant nicknames, laughing at classmates, and saying words that hurt others' feelings. This study employed a qualitative approach with a descriptive method. Data were collected through interviews and observations. The data were analyzed through data reduction, data presentation, and conclusion drawing. The findings revealed that verbal bullying was the most common form of bullying, while physical bullying was relatively mild but still had negative impacts on students. Victims of bullying tended to become quieter, less confident, more prone to crying, afraid of interacting with peers, and experienced a decline in learning motivation. Meanwhile, perpetrators generally displayed aggressive behavior, sought attention, and were influenced by family environments, peer groups, and social media The efforts made by teachers to prevent and address bullying included character education, fostering mutual respect, supervising students during learning and play activities, providing advice, guiding perpetrators, and collaborating with parents. Therefore, the role of teachers is crucial in creating a safe and supportive school environment for students.